Evaluation of the prevalence and prospective clinical impact of the JAK2 V617F mutation in coronary patients. Issue 3 (18th February 2014) - Muendlein, Axel; Gasser, Klaus; Kinz, Elena; Stark, Nicole; Leiherer, Andreas; Rein, Philipp; Saely, Christoph H.; Grallert, Harald; Peters, Annette; Drexel, Heinz; Lang, Alois H.
<x xml:space="preserve">Abstract</x> The JAK2 V617F mutation is not only found in the majority of patients with myeloproliferative neoplasms (MPN), including essential thrombocythemia (ET), but also has been reported in individuals without overt MPN. A close relation of the JAK2 V617F mutation to atherothrombotic events has been described, at least in patients with MPN. The prevalence of the JAK2 V617F mutation and its clinical impact in coronary patients is unknown. To address this issue, DNA samples from 1, 589 subjects undergoing coronary angiography with up to 11 years of follow up were genotyped using allele‐specific real‐time PCR assays. Prevalence of the JAK2 V617F mutation was 1.32% (n = 21) in coronary patients. Two JAK2 V617F positive patients showed baseline platelet counts indicative for ET and a third patient developed ET during follow up, finally resulting in a percentage of 0.188% of ET cases. This corresponds to an up to fivefold accumulation of ET cases in coronary patients compared with the general population. Our study showed no impact of the JAK2 V617F mutation on future atherothrombotic events or overall survival (HR = 1.04 [0.33–3.27]; P = 0.949 and HR = 0.35 [0.05–2.46]; P = 0.288, respectively). Therefore, our data suggest that JAK2 V617F positive coronary patients are not at increased risk for future atherothrombotic complications. Routine mutation screening in coronary patients is, therefore, not warranted. However, number of ET cases appears to be accumulated in coronary patients. For this reason, we recommend JAK2 V617F testing only in coronary patients showing abnormal blood cell counts for further clarification. Am. J. Hematol. 89:295–301, 2014. © 2013 Wiley Periodicals, Inc.